Bone Mineral Density in Women with Rheumatoid Arthritis and Related Factors: Controlled Study - Original Investigation - Nurdan Paker; Derya Soy Buğdaycı; Zeynep Akcan; Demet Tekdöş; Feride Sabırlı (Galenos Yayinevi, 2008)
Aim: The aim of this study was to analyse bone mineral density (BMD) in the patients with rheumatoid arthritis (RA) and to compare the results with those of control group's; to investigate the bone loss related factors. Material and Method: Sixty women with RA and 50 healthy subjects were included in the study. Control group consisted of age, sex and body mass matched healthy subjects. Bone density was measured at lumbar spine and proximal hip by DEXA (Lunar Dpx pro, Wisconsin, Madison). Demographic characteristics, DAS 28 and Health Assessment Questionnaire (HAQ) scores were enrolled. Z score £-1 was accepted as reduced BMD. Statistical analysis was performed with SPSS package program. Chi square test, t test and ANOVA were used for comparison. Results: Mean age was 51 years and disease duration was 77 months in the patient group. BMD at lumbar spine and hip in the RA patients was lower than those controls, but bone loss only lumbar spine was statistically significant higher in patient group (p<0,05). In the patient group the rate of reduced BMD at lomber spine and total femur were %31.6 and %21.6; the rate of osteoporosis at lomber spine and total femur were %13,3 and %5, respectively. Bone density showed significant correlation with functional capacity, age and weight in the patient group (p<0,05). Conclusion: In this study bone density at lumbar spine in women with RA was significantly lower than the control's. Bone loss showed relation with age, weight and physical capacity. (From the World of Osteoporosis 2008;14:29-34)